Transport of binary gases in nanoporous media with non-equilibrium adsorption - Kawthar A. Babatunde; Hamid Emami-Meybodi (Applied Surface Science Advances)
Surface diffusion and adsorption in nanoporous media are fundamental to mass transport and storage processes. The nanoporous media with high sorption affinity and slow mass exchange can exhibit non-equilibrium adsorption behavior. Accordingly, this study introduces a species-based model incorporating non-equilibrium adsorption kinetics for binary gas transport within nanoporous media. The proposed model for the predictive transport of gases incorporates non-equilibrium adsorption, surface diffusion, and bulk, viscous, and Knudsen diffusion. The extended Langmuir rate equation covers non-equilibrium adsorption, while the generalized Maxwell-Stefan equation addresses surface diffusion. The model is validated against two different experiments and then applied to simulate CO2 transport within methane-saturated nanoporous media, including organic-rich shales and coalbed methane. The simulation results reveal that the sorbed phase can occupy almost half of the pore volume. The comparison results between equilibrium and non-equilibrium adsorption models reveal that ignoring non-equilibrium sorption kinetics can lead to underestimating total mass flux and overestimating the sorbed-phase contribution of the mass flux. Using equilibrium adsorption can result in an underestimation of molar flux by 8%. The results of the molar flux ratio show that the sorbed phase adds three times more flux to the total flux when using the equilibrium adsorption model compared with the non-equilibrium adsorption model. This work demonstrates the impact of non-equilibrium adsorption on binary gas transport. The developed model gives a thorough framework for investigating gas transport and the sorbed phase’s contribution to the total mass transport.